Duck Eats Rabbit: Exactly Which Type of Relational Phrase Can Disambiguate the Perception of Identical Side by Side Ambiguous Figures?. (April 2018) - Mathewson, Kyle E.
Many individuals cannot at first see two ambiguous figures as different interpretations simultaneously, even with effort. Here in a large sample replication, we find that the phrase "duck eats rabbit" allows those who could not see a duck and rabbit side by side to do so. In a second experiment, we show that a relational phrase "next to" that does not disambiguate the spatial position interpretation does not similarly allow the duck to be seen next to the rabbit, supporting the proposal that top-down semantic-framing can influence perception of ambiguous figures.